Enhancing English Reading Comprehension and Critical Thinking through Murdoch Integrated Approach: A Language Education Study about Sustainable Development Goals (SDGs) - Weerawong, Prissana; Chano, Jiraporn; Wu, Chicheng (International Journal of Language Education, 2025)
This study investigated the impact of the Murdoch Integrated Approach (MIA) on improving English reading comprehension and analytical thinking among Thai Grade 5 students, in alignment with Sustainable Development Goal 4 on quality education. A one-group pretest-posttest design was implemented using eight structured learning plans over one semester. Two English reading tests were used to assess comprehension and analytical reading before and after the intervention. Results showed a significant improvement in both areas. These gains occurred because MIA promotes inquiry-based learning, active student engagement, and reflective thinking, enabling learners to interpret texts meaningfully and apply ideas critically. Although the absence of a control group requires cautious interpretation, the findings highlight the potential of MIA in enhancing essential language skills at the elementary level. This research contributes to language education by supporting pedagogical innovation aligned with global development goals.